2022
DOI: 10.31014/aior.1993.05.04.612
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Genre-Specific Strategy Instruction on the Writing Achievement of Fourth-Grade Students

Abstract: The quality of writing instruction is the primary determinant of writing acquisition. Revising and feedback are crucial aspects of the writing process. In this study, genre-specific strategy instruction was used as part of feedback and revision to develop the text structure and content of different text types in fourth grade. The study also examined whether the effect differed based on the genre and students' gender. Thirty students' first and final drafts of opinion, expository, and argumentative texts were a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The language skills learning techniques developed in this interactive multimedia also have a good effect on language skills acquisition. The planned writing evaluation model applied in this study contributed highly to the achievement of writing skills (Seban, 2022). This study observed "intercultural differences" as students with different backgrounds tried out other regional languages in the digital materials (Ou & Malmström, 2023) Regarding the limitations of the research, further studies need to be conducted to assess the effectiveness of interactive multimedia in real learning situations in order to get a scientific picture of the application of multicultural education with the internalization of religious moderation values.…”
Section: Discussionmentioning
confidence: 93%
“…The language skills learning techniques developed in this interactive multimedia also have a good effect on language skills acquisition. The planned writing evaluation model applied in this study contributed highly to the achievement of writing skills (Seban, 2022). This study observed "intercultural differences" as students with different backgrounds tried out other regional languages in the digital materials (Ou & Malmström, 2023) Regarding the limitations of the research, further studies need to be conducted to assess the effectiveness of interactive multimedia in real learning situations in order to get a scientific picture of the application of multicultural education with the internalization of religious moderation values.…”
Section: Discussionmentioning
confidence: 93%